Dicranum scottianum Turner (Dicranaceae): synonyms, a type and the correct author. (3rd April 2019) - Price, Michelle J.; Maier, Eva; Ellis, Leonard T.
ABSTRACT: Introduction . The moss Dicranum scottianum Turner, described based on material collected in Ireland by Robert Scott, is currently known from Europe and Macaronesia (Canary Islands and the Azores). The previously proposed authorship of 'Turner ex Robt. Scott' and lectotype for this name proved to be erroneous. Methods . Over 60 herbarium specimens, including types, of D. scottianum and putative allies were examined with the aim of outlining the diagnostic features of the taxon or taxa concerned, and establishing any necessary synonymy. Key results . The true authorship of Dicranum scottianum by Turner is re-established, and the name is effectively lectotypified with extant original material from BM. The type specimen and some subsequent collections of the species are described and illustrated. New nomenclatural synonyms of D. scottianum (namely Dicranum canariense Hampe ex Müll.Hal., D. erythrodontium Hampe ex Müll.Hal. and Orthodicranum allorgei J.J.Amann & Loeske) are detailed. Conclusions . Dicranum scottianum is characterised by its asymmetrical leaves with one side of the leaf wider than the other, the difference in the angle of insertion of the lamina with respect to the costa (one side of the leaf is inserted at a 45° angle and the other is plane but widely incurved), the laminal cells that are thick-walled with quadrate or rectangular lumina (seen in cross-section), and the wide and deep costa that has two bands of stereids.